Proses Kognitif Dalam Desain Pembelajaran Berbasis Masalah - Haris, Abdul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This paper aims to examine the theoretical concept of cognitive process involvement in the design of problem-based learning. Students face difficulties in designing learning, including in carrying out their role in managing learning such as the concept of